Susceptibility of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae Eucalyptus pest, to entomopathogenic fungi - Soliman, Everton Pires; Castro e Castro, Barbara Monteiro de; Wilcken, Carlos Frederico [UNESP]; Firmino, Ana Carolina [UNESP]; Ferreira Amaral Dal Pogetto, Mario Henrique; Barbosa, Leonardo Rodrigues; Zanuncio, Jose Cola (Univ Sao Paolo, 2019)
Thaumastocoris peregrinus Carpintero and Dellape (Hemiptera: Thaumastocoridae) is a sap-sucking insect that has become a major pest of eucalypts. The entomopathogenic fungi Beauveria bassiana (Bals.-Criv.) Vuill. and Metarhizium anisopliae (Metsch.) Sorokin have the potential to control insect pests. This study evaluated the susceptibility of T. peregrinus to two commercial products based on conidia of 8. bassiana and M. anisopliae. The fungi were sprayed onto adults of T. peregrinus at a concentration of 1 x 10(8) conidia mL(-1) to evaluate their pathogenicity and conidial production on the insect cadavers. Beauveria bassiana caused 100 % mortality, while M. anisopliae caused more than 80 % mortality of T peregrinus adults 11 days after fungi application. The fungi colonized the head and thorax regions and caused high mortality rates through conidial production. Pathogenicity of entomopathogenic fungi B. bassiana and M. anisopliae to T. peregrinus show potential to use these fungi in integrated pest management.
Keywords: Beauveria bassiana; Metarhizium anisopliae; biological control; bronze bug